Lung cancer incidence decreases with elevation: evidence for oxygen as an inhaled carcinogen - Simeonov, Kamen P.; Himmelstein, Daniel S. (PeerJ PrePrints, 2014)
The atmospheric concentration of oxygen, a driver of free radical damage and tumorigenesis, decreases sharply with rising elevation. To understand whether ambient oxygen concentrations play a role in human carcinogenesis, we characterized age-adjusted cancer incidence (compiled by the National Cancer Institute from 2005–2009) across counties of the elevation-varying Western United States and compared trends displayed by respiratory cancer (lung) and non-respiratory cancers (breast, colorectal, and prostate). To adjust for important demographic and cancer-risk factors, 8–12 covariates were considered for each cancer. We produced sensible regression models that captured known risks. Models demonstrated that elevation strongly, negatively associates with lung cancer incidence (p < 10−16), but not with incidence of non-respiratory cancers. For every 1000 meter rise in elevation, lung cancer incidence decreased by 7.23 [99% CI: 5.18–9.29] cases per 100,000 individuals, equivalent to 12.7% of the mean incidence, 56.8. As a predictor of lung cancer incidence, elevation was second only to smoking prevalence in terms of significance and effect size. Furthermore, no evidence of uncontrolled confounding or ecological fallacy was detected: the lung cancer association was robust to varying regression models, county stratification, and population subgrouping; additionally seven environmental correlates of elevation, such as exposure to sunlight and fine particulate matter, could not capture the association. Overall, our findings suggest the presence of an inhaled carcinogen inherently and inversely tied to elevation, offering epidemiological support for oxygen-driven tumorigenesis. Finally, highlighting the need to consider elevation in studies of lung cancer, we demonstrated that previously reported inverse lung cancer associations with radon and UVB became insignificant after accounting for elevation.
Keywords: Cancer Incidence; Lung Cancer; Altitude; Elevation; Oxygen